An evaluation of the opt-out approach to Hepatitis C Virus infection testing in prisons - Jack, Kathryn (2020)
The research in this thesis presents insights into elements of healthcare provided in micro-communities that are hidden from public view; prisons in England. Prisons are a key demographic in NHS England’s drive to eliminate hepatitis C virus infection (HCV) as a major public health threat by 2025. A policy to offer blood borne virus testing, with HCV as the priority, to those entering prisons via an opt-out approach was launched in 2014. This policy was implemented in the East Midlands prison estate, comprising 14 establishments, using dried blood spot tests as the default method of obtaining samples for analysis. The research aimed firstly to measure the impact of the opt-out testing policy on HCV test uptake in the East Midlands prisons and secondly to generate explanatory theories, based on the perspectives of men serving prison sentences, which would underpin future interventions to maximise test uptake in prisons.